Representation of Rajawali Citra Televisi Indonesia and Indosiar Social Cognition of Journalist in the Construction of Discourse on Corruption News - Novitasari, Nia; Mardikantoro, Hari Bakti (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Discourse analysis of corruption news is not enough just based on the aspect of text analysis, but rather how a text is produced. Therefore, it takes a study of the representation of social cognition. This study aims to interpret the social cognition of Rajawali Citra Televisi Indonesia (RCTI) and Indosiar journalists in constructing a discourse on corruption reporting. The data in qualitative research is obtained through the method of listening and interviewing. The techniques in the listening method used include the technique of free listening involved in interview, recording technique, and note-taking techniques. Meanwhile, in the interview method, the technique used is the direct interview technique and the indirect interview techniques. The data analysis technique used in this study is the Critical Discourse Analysis (CDA) of Teun A. van Dijk. The results of the study showed that in the news discourse corruption was constructed by RCTI and Indosiar using person schemes, self schemes, role schemes, and event schemes. The use of these schemes to support broadcast news values. In social cognition, journalists play a role as social control and communicator to preach the dominant discourse that develops in society. This research is useful for the development of discourse science and becomes a reference material for the community in understanding the characteristics of a media.